Effect of nonlinear wave collapse on line shapes in a plasma. (18th May 2016) - Hannachi, I.; Stamm, R.; Rosato, J.; Marandet, Y.
Abstract: The nonlinear interaction of waves can change the structural and radiative properties of plasmas. We describe the main features of a fully ionized unmagnetized plasma affected by strong Langmuir turbulence characterized by nonlinear wave collapse, and propose a simple model for evaluating the changes expected on a hydrogen line shape affected by such conditions. Our model is based on a stochastic renewal model using an exponential waiting time distribution and a half-normal probability density function for the electric-field magnitude of the turbulent wave packet. The first results obtained with a simulation calculation of the hydrogen line show that strong Langmuir turbulence can provide an additional broadening to a Stark profile.